The Features of the Circle of Willis on Multislice Computed Tomography in Humans Without Cerebral Vascular Malformations - Van Ngoc, Doan; Anh Tuan, Tran; Dinh Au, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Abstract: A study of 135 cases without cerebral vascular malformations who were scan MSCT of cerebral arteries at Bach Mai hospital during the period from January 2019 to December 2019. Result: mean diameter of cerebral artery segments: left and right A1 segments: 2.28 ± 0.47 and 2.19 ± 0.53 mm; AcomA: 1.71 ± 0.68 mm; left and right M1 segments: 2.82 ± 0.46 mm and 2.8 ± 0.49 mm; left and right PcomA: 1.62 ± 0.5 mm and 1.67 ± 0.48 mm; left and right P1 segments: 2.22 ± 0.49 mm and 2.22 ± 0.56 mm; left and right P2 segments: 2.32 ± 0.38 mm and 2.35 ± 0.36 mm; BA: 3.41 ± 0.69 mm. The diameters of the cerebral arteries were similar in both sexes, with no difference on the right and left sides of the ring of Willis. The diameter of the edges of the Willis circle varied from aplastic and hypoplastic, which was mainly seen in the AcomA, PcomA, the A1 segment of the anterior cerebral artery, and P1 of the posterior cerebral artery. The transformations of the Willis ring included 17 forms, of which four simple transformations of the anterior part, four simple transformations of the posterior part, and nine combined transformations between the anterior and posterior parts. Mainly found aplasia or hypoplasia of the AcomA 14.1% and the PcomA 12.6%. Conclusion: the index of normalization of the segments of the Willis polygon and its variant forms contributed to bolder intervention planning in cerebrovascular disease treatment. Keywords: Circle of Willis, Cerebral arteries, MSCT.